NANOTECHNOLOGY AS AN ADSORBENT FOR THE HEAVY METAL (Fe): LITERATURE REVIEW - Utari Rahmatillah; Riki Mefta Firwanda; Nurhayati (Indonesian Journal of Environmental Sustainability, 2023)
This research was a literature study that aims to understand the application of nanoparticles as heavy metal adsorbents, explore the role of nanoparticle technology in the context of environmental protection and human health, and identify effective nanotechnology. Industrial waste containing the heavy metal Fe can pose a serious threat to the environment and human health. In this study, we evaluated various literature sources discussing the use of nanoparticles, especially activated carbon, as effective adsorbents for removing heavy metals from water and waste. The results of literature studies show that the application of nanoparticles as adsorbents can increase the efficiency of filtration and heavy metal removal, which in turn contributes to environmental protection and human health. Additionally, this research identifies the important role of nanoparticle technology in various aspects, including water treatment, air pollution control, environmental monitoring, and the development of safer medicines. With proper application, nanoparticle technology can help reduce the risk of exposure to heavy metals and other pollutants, as well as improve water and air quality, which has a positive impact on human health and environmental sustainability. Identification of these most effective nanotechnologies can help guide the development of better solutions in the context of environmental protection and human health. This research provides deeper insight into the positive role of nanoparticle technology in addressing the environmental and health challenges faced by society.